On the Basic Categories of Facilitative Pedagogy - Avdeeva, Irina (2020)
A key characteristic of a learner-centered educational process is its realization as a subject-to-subject interaction between participants. At present, a view that the goal of the pedagogical process is to create conditions for the development of a creative and moral personality, independent in cognitive and practical activities, free to choose a professional, social, family career can be considered customary. A rounded actualized personality is, first of all, the subject of human relations and conscious self-work. That is, this is a person who has a conscious and stable system of relations to themselves and the world, who is able to realize the motives of their activities, set a goal, and independently regulate their own actions to achieve it. A teacher positions oneself as a facilitator in this interaction, and a firm promotion of the student’s ability to be the subject of one’s own relationships, behavior, becomes the main principle of professional work of both each teacher taken separately and the teaching staff as a whole.